Cork & Fuzz. The babysitters - Chaconas, Dori, 1938-; McCue, Lisa (New York : Viking, 2010)
Cork the muskrat tries to persuade his best friend Fuzz, a possum, to help babysit for a porcupine.
Some copies issued in 2014 as a paperback.
Keywords: Babysitters -- Juvenile fiction; Opossums -- Juvenile fiction; Muskrat -- Juvenile fiction; Porcupines -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction